The Preliminary Study on a Legal Framework Acceptance Relate to Halal Tourism in Lake Toba - Hadyan Yunhas Purba, M.; Natasya Sirait, Ningrum; Patriana Yuswar, Cheryl; Kanni Ramaiah, Angayar; Azmi, Azila; Abdullah , Azrul (KnE Social Sciences, 2024)
Halal tourism is one form of tourism development and promotion that is anticipated to boost local economic growth and state revenue. Halal tourism aims to instill trust in Muslim visitors so that they are not hesitant to visit tourist destinations like Lake Toba where the majority of the population is non-Muslim and is one of the most popular tourist destinations. This is done to convince the tourists that these destinations welcome Muslim visitors even if Lake Toba’s population is primarily comprised of non-Muslims. The government must enact rules if halal tourism is to be practiced properly and lawfully. This study used normative and empirical research methods. Examining the rules and laws governing halal goods and tourism is done as normative research. Following surveys and interviews with villagers and business owners in the Lake Toba region, empirical research was conducted. The findings demonstrate that halal tourism is a concept that ensures the provision of the services and infrastructure required by Muslim travelers during their journey, including halal food, prayer spaces, and so forth. However, halal tourism currently has legal loopholes. Halal tourism in Lake Toba thus has advantages and disadvantages. In reality, local residents and business owners in the Lake Toba region are sympathetic to the notion, as long as it does not obliterate traditions and local culture, and does not act as a campaign to Islamize them. As a tourism marketing tactic, Indonesia can model its halal tourism policies after those of Malaysia. Keywords: preliminary study, legal frameworks, halal tourism